STRENGTHENING MSME CAPABILITY THROUGH COMMUNITY-BASED HR MAPPING IN MALANG - Misbahuddin Azzuhri; Dian Ari Nugroho; Aji Purba Trapsila; M. Mukhlis Amrullah; Muhammad Fajrul Islam F; Naima Andleeb (EMPOWERING HUMANITY, 2026)
This community service program aimed to strengthen MSME capacity through a community based HR needs-mapping approach that served as the foundation for targeted capacity-building interventions. The program was implemented in collaboration with Perumda Tugu Aneka Usaha and involved 50 MSME actors. HR needs were assessed using structured surveys, focus group discussions (FGD), and field observations. Based on the mapping results, a series of activities was conducted, including basic HR management training focusing on role clarification and simple standard operating procedure (SOP) development, followed by the establishment of MSME learning communities organized by business sector and geographic proximity. The findings revealed that digital literacy represented the strongest capability among participants, whereas managerial practice and community engagement exhibited the largest competency gaps, indicating priority areas for capacity development. Program evaluation demonstrated improved role clarity, initial adoption of basic HR management practices, and stronger collaboration among participating MSME through the newly established learning communities. The program produced a community-based HR needs-mapping model integrating HR capability, managerial practice, digital literacy, and community engagement. This model provides a practical and evidence-based framework for designing sustainable MSME capacity building programs that can be adopted by local governments, development agencies, and other institutions supporting MSME development.